2015
DOI: 10.1111/jbi.12494
|View full text |Cite
|
Sign up to set email alerts
|

Miocene extensional tectonics explain ancient patterns of diversification among turret‐building tarantulas (Aphonopelma mojave group) in the Mojave and Sonoran deserts

Abstract: Aim Phylogeographical studies in the Mojave and Sonoran deserts often find genetic discontinuities that pre-date the Pleistocene. A recent synthesis of phylogeographical data, called the Mojave Assembly Model, provides a hypothesis for the historical assembly of these desert biotas but does not adequately capture the complexity of pre-Pleistocene vicariance events. We tested this model and assessed pre-Pleistocene divergences by exploring the phylogeography of the Aphonopelma mojave group, which is composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…While using only maternally inherited mtDNA for population genetic analyses may have potential shortcomings (Edwards & Bensch, ), the lineages evaluated here are phylogenetically strongly supported by multilocus data (Xu et al ., ). MtDNA is also widely used in phylogeographical studies of other spiders with lifestyles comparable to liphistiids (Hamilton et al ., ; Graham et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…While using only maternally inherited mtDNA for population genetic analyses may have potential shortcomings (Edwards & Bensch, ), the lineages evaluated here are phylogenetically strongly supported by multilocus data (Xu et al ., ). MtDNA is also widely used in phylogeographical studies of other spiders with lifestyles comparable to liphistiids (Hamilton et al ., ; Graham et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…Geographically, species vary in the amount of genetic divergence that occurs at the river. There is complete differentiation observed for the turret‐building tarantula ( Aphonopelma prenticei ; Graham, Hendrixson, Hamilton, & Bond, ), round‐tailed ground squirrel ( Xerospermophilus tereticaudus ; Bell, Hafner, Leitner, & Matocq, ) and leopard frogs ( Lithobates onca & L. yavapaiensis ; Oláh‐Hemmings et al, ). In contrast, there is little river‐based differentiation in the desert pocket mouse ( Chaetodipus penicillatus ; Jezkova, Jaeger, Marshall, & Riddle, ), Arizona hairy scorpion ( Hadrurus arizonensis ; Graham, Jaeger, Prendini, & Riddle, ), and bighorn sheep ( Ovis canadensis , Nelson; Buchalski et al, ), among others.…”
Section: Geological and Biological Backgroundmentioning
confidence: 99%
“…Many species exhibit divergence associated with the ecological boundary dividing the Mojave and Sonoran deserts (Mojave‐Sonoran “ecotone”). Of studies referencing ecotone divergence (Inman et al, ; Wood, Fisher, & Vandergast, ), most attribute this to the vegetation transition (Devitt, ; Graham et al, ; Jezkova et al, ; Mulcahy, Spaulding, Mendelson, & Brodie, ; Wood et al, ) despite the likelihood of an underlying abiotic control (a proximate mechanism) on the change in plant composition. The Mojave Desert has higher average elevation, a wider range of annual temperatures, and lower annual precipitation compared to the Sonoran Desert (Norris, ).…”
Section: Geological and Biological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…68 In addition to improving our understanding of deeper phyloge-69 netic relationships, DNA sequence data have played a crucial role 70 in uncovering and recognizing species-level diversity in mygalo-71 morphs. Recent genetic studies have revealed ancient but morpho-72 logically cryptic species diversity in various mygalomorph groups 73 (Starrett and Hedin, 2007;Stockman and Bond, 2007;Hedin and 74 Carlson, 2011; Graham et al, 2015). Thus far, most genetic studies 75 have relied principally on one or two fragments of mitochondrial 76 DNA.…”
Section: Dna Barcoding 23mentioning
confidence: 99%